1996
DOI: 10.1007/bf00167181
|View full text |Cite
|
Sign up to set email alerts
|

Functional regulation by dopamine receptors of serotonin release from the rat hippocampus: in vivo microdialysis study

Abstract: The functional regulation by dopamine (DA) receptors of serotonin (5-HT) release from the rat hippocampus was investigated by use of in vivo microdialysis. Dialysate 5-HT levels were reduced by co-perfusion of 10 microM tetrodotoxin (TTX) and were elicited by K+ (60 and 120 mM) stimulation in a concentration-dependent manner. Local perfusion (10 microM) and peripheral administration (20 mg/kg, i.p.) of fluoxetine produced increases in 5-HT levels. These results indicate that the spontaneous 5-HT levels in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…These anatomical results suggest that DA input to the DR may play a critical role in the regulation of the function of DR 5-HT neurons. Consistent with this notion, in vivo neurochemical studies have reported that administration of DA receptor agonists increases the synthesis and release of 5-HT in the DR (Ferré et al, 1994;Matsumoto et al, 1996). Direct evidence for a role of DA in the regulation of 5-HT neurons function comes from recent in vitro electrophysiological study showing that activation of DA receptors induces a membrane depolarization and thereby increases the excitability of DR 5-HT neurons (Haj-Dahmane, 2001).…”
mentioning
confidence: 83%
“…These anatomical results suggest that DA input to the DR may play a critical role in the regulation of the function of DR 5-HT neurons. Consistent with this notion, in vivo neurochemical studies have reported that administration of DA receptor agonists increases the synthesis and release of 5-HT in the DR (Ferré et al, 1994;Matsumoto et al, 1996). Direct evidence for a role of DA in the regulation of 5-HT neurons function comes from recent in vitro electrophysiological study showing that activation of DA receptors induces a membrane depolarization and thereby increases the excitability of DR 5-HT neurons (Haj-Dahmane, 2001).…”
mentioning
confidence: 83%
“…Much less data exist as to whether DA exerts regulation over 5-HT release, and it is not clear whether this regulation would be excitatory or inhibitory (Ferré et al, 1994;Matsumoto et al, 1996;Ferré and Artigas, 1993;Thorré et al, 1998). This could be taken as evidence for a hierarchical arrangement between 5-HT and DA, with the former exerting its effects by manipulating the latter.…”
Section: The Dopaminergic Systemmentioning
confidence: 99%
“…Activation of 5-HT2A and 5-HT3 receptors, via mediation by GABA neurons, inhibits the release of prefrontal neocortical DA, however activation of 5-HT3 receptors also increases DA release in the nucleus accumbens and the medial prefrontal cortex (mPFC) (Di Matteo et al, 2008;Fink & Göthert, 2008). DA also regulates 5-HT through projections from DA nuclei to the dorsal raphé nucleus (DR), by DA neurones within the DR or more indirectly, via action of D2 receptors on NA neurons (Matsumoto et al, 1996;Adell et all, 2010).…”
Section: Functional Interactions Between Neurotransmitter Systemsmentioning
confidence: 99%